Decolonising English Classrooms: Reclaiming Space through Indian Literature in Translation - Murthy, V. (University of Jaffna, 2025)
The process of decolonising English classrooms necessitates a critical re evaluation of curricula that have long been dominated by Eurocentric / Anglocentric literary traditions. This paper explores how Indian literature in translation serves as a powerful tool for reclaiming intellectual and cultural space within English studies. By incorporating diverse linguistic and literary traditions from India, educators can challenge the hegemony of Western literary canons and foster a more inclusive and representative pedagogy. Indian literature in translation provides students with access to regional narratives, oral traditions, and indigenous knowledge systems that are often marginalised in the mainstream English curricula. Texts by writers such as Premchand, Bama, Salma, Sukirthan Rani, Devanooru Mahadeva and Mahasweta Devi offer insights into caste, gender, resistance, and postcolonial identity, enriching students’ engagement with literature beyond the confines of British and American texts. This study examines the pedagogical impact of integrating such texts into English classrooms, focusing on how they reshape students’ perceptions of language, power, and literary value. Through qualitative research, this paper examines the impact of Indian literature in translation on undergraduate students and teachers who have engaged with these texts. Using in-depth interviews, the study captures their perspectives on how exposure to regional narratives influences their understanding of literature, identity, and cultural diversity. This paper argues that reclaiming space through Indian literature in translation is not merely an act of diversification but a crucial step toward decolonising English studies. It highlights how such interventions empower students to question established hierarchies, recognise the legitimacy of non-Western literary traditions, and actively participate in a more equitable and dynamic literary discourse.
Keywords: Decolonisation; Indian literature in translation; English studies; Pedagogy; Postcolonialism; Curriculum reform